PENGARUH CITRA MEREK, KUALITAS PRODUK, PERCIEVED PRICE FAIRNESS, STRATEGI DIFERENSIASI TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN TUGU CHOCOLATE DI KOTAGEDE YOGYAKARTA - betty dwi gumelar (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The research was conducted in order to test the variable influence the image of a brand , the product quality, Perceived price fairness, strategy differentiation of the decision the purchase by tugu chocolate in kotagedeyogyakarta. This research use special variable indenpenden the image brand, quality products, perceived price fairness, strategy differentiation and dependent variable the decision the purchase. Sampling techniques used is simple random sampling . The technique of simple random sampling ( a random sample of simple ) which is that type the sampling method of the probability , where is group of researchers from for selecting villagers to unsupported sample or temporary resident and gives had the same opportunities to all the members of the population to set forth as a member of the sample . Sample only taken on the consumer tugu chocolate in kotagedeyogyakarta which were 100 people. Data collection procedures using koesioner distributed to be filled by consumers in chocolate . For testing validity and realibilitas variable using the tools spss 16.0. And smartpls 3.0. Based on the analysis of the data and the results of the testing of hypotheses on this research it can be concluded that the image of a brand it has some positive effects of the decision of a purchase with the level of the significance of the level of 0,000 . Decision will not affect the quality products with the purchase of 0,180 significance .Percieved price fairness it has some positive effects of the decision of the 0,001 significance . Strategy differentiation do not affect of the decision a purchase with level 0,947 significance . Simultaneously where i am the image of a brand , the product quality , he said telkomsel would perceived fairness the minister said , a strategy of differentiation it has some positive effects of the decision of a purchase with the level of significance of the 0.000 and the level of errors in 5 % .